2016
DOI: 10.1002/da.22486
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Means Access and Assessment Among Suicidal Emergency Department Patients

Abstract: Background Reducing access to lethal means (especially firearms) might prevent suicide, but counseling of at-risk individuals about this strategy may not be routine. Among emergency department (ED) patients with suicidal ideation or attempts (SI/SA), we sought to describe home firearm access and examine ED provider assessment of access to lethal means. Methods This secondary analysis used data from the Emergency Department Safety Assessment and Follow-up Evaluation, a 3-phase, 8-center study of adult ED pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 32 publications
2
54
1
Order By: Relevance
“…Prior work, including the large ED-Safety Assessment and Follow-up Evaluation (ED-SAFE) trial, documents that ED clinicians often do not routinely counsel about lethal means 21,22,3336 and their counseling can be improved. 37 Even with political sensitivities about guns, 38 patients are receptive to receiving guidance, 19,3941 and counseling can improve storage practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work, including the large ED-Safety Assessment and Follow-up Evaluation (ED-SAFE) trial, documents that ED clinicians often do not routinely counsel about lethal means 21,22,3336 and their counseling can be improved. 37 Even with political sensitivities about guns, 38 patients are receptive to receiving guidance, 19,3941 and counseling can improve storage practices.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,42 ED-SAFE chart reviews found that although 11% of patients reported having firearms only 50% of those patients had medical record notes indicating lethal means counseling. 22 Other evidence indicates that providing safety devices with counseling enhances results. 43 Future research should examine the effectiveness of safety messages, with and without providing safety devices and also consider the effectiveness of new “extreme risk protection orders” for temporary removal of guns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 As firearm suicide has a case fatality rate of 90%, versus 10% for all other methods combined, 4,62,63 reducing access to firearms and other lethal means among those with suicide risk may prevent suicide deaths, 64 and is part of the National Strategy for Suicide Prevention. 65 Lethal means screening and counseling (i.e., counseling about reducing access to lethal means) for suicidal ED patients is recommended, 66,67 and provider training adapted for EDs exists 68 , but there are gaps in current research to guide ED implementation 35,60,61,69 and efficacy 67,70 . Barriers to address include ED providers' unfamiliarity with options for safe firearm storage, inadequate provider training on counseling, 59 and unanswered questions about the best messages and messengers for the counseling.…”
Section: Suicide (Table 2)mentioning
confidence: 99%
“…Screening and counseling about firearms is uncommon, whether as anticipatory guidance (46) or a selective intervention (47)(48)(49). For example, in a study of veterans who screened positive for suicidal thoughts, only 15% of providers documented whether patients had access to firearms (50).…”
Section: Barriersmentioning
confidence: 99%